2009
DOI: 10.3390/s91209816
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Sensing by Nanoporous Crystalline Polymers

Abstract: Chemical sensors are generally based on the integration of suitable sensitive layers and transducing mechanisms. Although inorganic porous materials can be effective, there is significant interest in the use of polymeric materials because of their easy fabrication process, lower costs and mechanical flexibility. However, porous polymeric absorbents are generally amorphous and hence present poor molecular selectivity and undesired changes of mechanical properties as a consequence of large analyte uptake. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 118 publications
0
60
0
Order By: Relevance
“…These materials can detect organic compounds or low-molecular-mass substances present in gaseous and liquid environments. For instance, Pilla et al [211] showed how 1-lm-thick s-PS films (porosity: 7%; pore size: not specified) can work as gravimetric sensors for the detection of chloroform in both vapor and liquid phases.…”
Section: Nmmentioning
confidence: 99%
“…These materials can detect organic compounds or low-molecular-mass substances present in gaseous and liquid environments. For instance, Pilla et al [211] showed how 1-lm-thick s-PS films (porosity: 7%; pore size: not specified) can work as gravimetric sensors for the detection of chloroform in both vapor and liquid phases.…”
Section: Nmmentioning
confidence: 99%
“…These nanoporous crystalline forms were found to have the capability to absorb molecules like CO 2 and H 2 [44,45] as well as organic molecules [16,46]. Hence, these materials can be used as sensors, [47][48][49][50] molecular sieves, [46,[51][52][53], catalysts [54], etc.…”
Section: Introductionmentioning
confidence: 97%
“…These microporous-crystalline polymers are able to absorb volatile organic compounds (VOC) also when present in traces and have been mainly proposed for molecular separation [22][23][24][25][26][27], sensor [28] and catalysis [29][30][31] applications. In particular two different microporous crystalline forms, named δ [10-13, 16, 17] and ε [14], have been thoroughly described for s-PS.…”
Section: Introductionmentioning
confidence: 99%